Teaching NeuroImage: Crowned Dens Syndrome: An Acute Attack of Calcium Pyrophosphate Deposition Disease Mimicking Acute Meningitis. (6th September 2022) - Francia, Alessandro; Conte, Giorgio; Platania, Giulia; Arighi, Andrea; Pietroboni, Anna Margherita; Fumagalli, Giorgio Giulio; Floro, Stefano; Scarpini, Elio; Galimberti, Daniela; Saetti, Maria Cristina; Carandini, Tiziana
Abstract : An 88-year-old man presented with acute onset of severe neck pain, meningismus, headache, and fever (up to 38°C). Blood tests showed raised inflammatory markers, but CSF analysis was not suggestive of CNS infection (Table). Autoimmune antibodies were negative. Cervical spine CT showed calcifications of the transverse ligament of the atlantoaxial joint with inflammatory changes revealed by cervical spine MRI (Figure). Clinical presentation and biochemical and radiologic findings were all consistent with crowned dens syndrome. 1, 2 Symptoms and inflammatory markers promptly decreased after a brief course of anti-inflammatory treatment. Recognition of this syndrome is important to differentiate it from other infectious or autoimmune diseases and avoid unnecessary treatment.